Close but not too close: opposition network strategy and democratization in Zambia. (2nd January 2023) - Pinckney, Jonathan
ABSTRACT: Current literature finds that democratization is most likely when opposition social movements have initiated a political transition. Yet little work has disaggregated bottom-up transitions to suggest when this effect obtains. This article examines a case not widely known in the social movements' literature: the 1991 political transition in Zambia. It proposes a novel theoretical avenue to help explain this case's incomplete democratic transition. The piece re-conceptualizes the opposition movement as a multi-organizational actor network. I argue that opposition movements face strong incentives to unify through either centralizing around a single organization or creating a dense network of multiple, overlapping connections. The strategy they pursue affects the transitional political landscape. Highly centralized opposition networks are likely to lead to less democratic outcomes while dense decentralized networks will have more democratic outcomes. I find that high centralization by the opposition in Zambia undermined political accountability during the transition and limited Zambia's democratic progress.